Review of bioinspired composites for thermal energy storage: preparation, microstructures and properties - Yu, Min; Wang, Mengyuan; Xu, Changhao; Zhong, Wei; Wu, Haoqi; Lei, Peng; Huang, Zeya; Fu, Renli; Gucci, Francesco; Zhang, Dou (MDPI, 2025)
Bioinspired composites for thermal energy storage have gained much attention all over the world. Bioinspired structures have several advantages as the skeleton for preparing thermal energy storage materials, including preventing leakage and improving thermal conductivity. Phase change materials (PCMs) play an important role in the development of energy storage materials because of their stable chemical/thermal properties and high latent heat storage capacity. However, their applications have been compromised, owing to low thermal conductivity and leakage. The plant-derived scaffolds (i.e., wood-derived SiC/Carbon) in the composites can not only provide higher thermal conductivity but also prevent leakage. In this paper, we review recent progress in the preparation, microstructures, properties and applications of bioinspired composites for thermal energy storage. Two methods are generally used for producing bioinspired composites, including the direct introduction of biomass-derived templates and the imitation of biological structures templates. Some of the key technologies for introducing PCMs into templates involves melting, vacuum impregnation, physical mixing, etc. Continuous and orderly channels inside the skeleton can improve the overall thermal conductivity, and the thermal conductivity of composites with biomass-derived, porous, silicon carbide skeleton can reach as high as 116 W/m*K. In addition, the tightly aligned microporous structure can cover the PCM well, resulting in good leakage resistance after up to 2500 hot and cold cycles. Currently, bioinspired composites for thermal energy storage hold the greatest promise for large-scale applications in the fields of building energy conservation and solar energy conversion/storage. This review provides guidance on the preparation methods, performance improvements and applications for the future research strategies of bioinspired composites for thermal energy storage.
Keywords: 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy; thermal energy storage; bioinspired composites; phase change materials (PCMs); preparation process; heat storage properties